1, 1, 1-Trifluoropropan-2-ammonium triflate enantiomers: stereoselective synthesis and direct use in reaction with epoxides. Issue 4 (15th April 2017) - Packer, Gemma; Malassis, Julien; Wells, Neil; Light, Mark; Linclau, Bruno
Graphical abstract: Abstract: A three-step synthesis of enantiomerically enriched 1, 1, 1-trifluoro-2-propanamine based on the use of a chiral sulfinamide auxiliary is described. The reduction of the geometrically pure Z -sulfinimine (NOE, HOE) with NaBH4 orl -Selectride leads to the corresponding ( R )- or ( S )-configured amine derivatives (X-ray crystallographic analysis) with 92–96% de . The typical models to explain the stereoselection for these reducing agents fail to rationalize the obtained stereoselectivities, and an in situ imine isomerization is proposed to occur. The direct use of the hydrochloric acid salt (with excess Et3 N) of this poorly nucleophilic amine for epoxide opening reactions is not possible due to the higher nucleophilicity of chloride. Hence, a novel triflate salt is introduced, synthesized through ready sulfinamide hydrolysis with trimethylsilyl triflate, which can be used directly, without the need of isolating the pure amine beforehand. Abstract : ( R S )- N -((2 R )-1, 1, 1-Trifluoroprop-2-yl)- t -butanesulfinamide: C7 H14 F3 NOS [ α ]D 22  = −70.4 ( c 0.99, CHCl3 ) 96:4 dr sample Source of chirality: the auxiliary Absolute configuration: ( R S, R ) Abstract : ( R S )- N -((2 S )-1, 1, 1-Trifluoroprop-2-yl)- t -butanesulfinamide: C7 H14 F3 NOS [ α ]D 22  = −68.8 ( c 0.99, CHCl3 ) Source of chirality: the auxiliary Absolute configuration: ( R S, S ) Abstract : ( R )-1, 1, 1-Trifluoro-2-propanamine hydrochloride: C3 H7 ClF3 N [ α ]D 23  = −1.15 ( c 1.0, MeOH) Source of chirality: the auxiliary Absolute configuration: ( R ) Abstract : ( R )-1, 1, 1-Trifluoro-2-propanamine hydrogen triflate: C4 H7 F6 NO3 S [ α ]D 22  = +0.3 ( c 0.64, MeOH) Source of chirality: the auxiliary Absolute configuration: ( R )